2010
DOI: 10.1371/journal.pone.0013890
|View full text |Cite
|
Sign up to set email alerts
|

Early Acquisition of Neural Crest Competence During hESCs Neuralization

Abstract: BackgroundNeural crest stem cells (NCSCs) are a transient multipotent embryonic cell population that represents a defining characteristic of vertebrates. The neural crest (NC) gives rise to many derivatives including the neurons and glia of the sensory and autonomic ganglia of the peripheral nervous system, enteric neurons and glia, melanocytes, and the cartilaginous, bony and connective tissue of the craniofacial skeleton, cephalic neuroendocrine organs, and some heart vessels.Methodology/Principal FindingsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 80 publications
(109 reference statements)
5
74
0
Order By: Relevance
“…The migrated cells from rosettes in the present study showed similar expression of MSC markers, as was observed in other studies (2,34,58). However, while a previous report showed that human ES cell-derived NCSCs do not express CD73 (31), our migrated cells exhibited higher levels of CD73 expression, in consistent with previous reports (8,58). Further analyses are required to examine the differences between iPS cell-derived and ES cell-derived NCCs in terms of CD73 expression.…”
Section: Discussionsupporting
confidence: 92%
“…The migrated cells from rosettes in the present study showed similar expression of MSC markers, as was observed in other studies (2,34,58). However, while a previous report showed that human ES cell-derived NCSCs do not express CD73 (31), our migrated cells exhibited higher levels of CD73 expression, in consistent with previous reports (8,58). Further analyses are required to examine the differences between iPS cell-derived and ES cell-derived NCCs in terms of CD73 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous microarray gene expression analysis of hESC-derived multipotent NPCs (11,30,31) suggested that SOX2 regulates the expression of LIN28, a well-studied repressor of let-7 family biosynthesis (13-16). Immunofluorescence analysis confirmed that SOX2 and LIN28 were coexpressed in all NPCs (Fig.…”
Section: Sox2mentioning
confidence: 99%
“…These cells express the neural crest specifier SOX10 and clonal analysis indicates they are multipotent. Importantly, when these cells are injected in chick embryos, they migrate normally and contribute to the same derivatives as endogenous neural crest cells (Curchoe et al 2010).…”
Section: Neural Crest Cells and Diseasementioning
confidence: 99%